Obiective de dezvoltare privind creşterea calităţii guvernării – România 2015–2035 - Marin, Monica; Neguţ, Adriana; Petrescu, Claudia; Stănculescu, Manuela Sofia; Stănescu, Iulian (Calitatea Vieții, 2015)
This material sets out some specific objectives related to the general objective of developing the quality of the public administration as a necessary condition for improving the quality of public services delivery and more generally, to better governance. The objectives are based on desk-research of national and international strategic documents and available datasets. These objectives relate to: i) public policy making and implementation; ii) human resources management and iii) e-government, as well as key enablers related to development of partnership capacity and the process of fiscal and administration decentralization. In order to monitor implementation of these objectives on the short, medium and long term, this material puts forward a series of key indicators to track Romania’s progress in attaining the general objective. The proposed targets cannot be reached if the following short-term objectives are not achieved: (i) improving the quality of statistics in the public sector; ii) development of the systems of awards and benefits for the public personnel; iii) implementing the European funded projects that target the training of public personnel; iv) increased financial and decisional autonomy of local public authorities; v) simplification of administrative procedures for accessing public services by the citizens; vi) improving digital competences of people from disadvantaged groups.